Autophagy Proteins ATG5 and ATG7 Are Essential for the Maintenance of Human CD34+ Hematopoietic Stem‐Progenitor Cells. (28th March 2016) - Gomez‐Puerto, Maria Catalina; Folkerts, Hendrik; Wierenga, Albertus T.J.; Schepers, Koen; Schuringa, Jan Jacob; Coffer, Paul J.; Vellenga, Edo
Abstract : Autophagy is a highly regulated catabolic process that involves sequestration and lysosomal degradation of cytosolic components such as damaged organelles and misfolded proteins. While autophagy can be considered to be a general cellular housekeeping process, it has become clear that it may also play cell type‐dependent functional roles. In this study, we analyzed the functional importance of autophagy in human hematopoietic stem/progenitor cells (HSPCs), and how this is regulated during differentiation. Western blot‐based analysis of LC3‐II and p62 levels, as well as flow cytometry‐based autophagic vesicle quantification, demonstrated that umbilical cord blood‐derived CD34 + /CD38 − immature hematopoietic progenitors show a higher autophagic flux than CD34 + /CD38 + progenitors and more differentiated myeloid and erythroid cells. This high autophagic flux was critical for maintaining stem and progenitor function since knockdown of autophagy genes ATG5 or ATG7 resulted in reduced HSPC frequencies in vitro as well as in vivo. The reduction in HSPCs was not due to impaired differentiation, but at least in part due to reduced cell cycle progression and increased apoptosis. This is accompanied by increased expression of p53, proapoptotic genes BAX and PUMA, and the cell cycle inhibitor p21, as well as increased levels of cleaved caspase‐3 and reactive oxygen species. Taken together, our data demonstrate that autophagy is an important regulatory mechanism for human HSCs and their progeny, reducing cellular stress and promoting survival. Stem Cells 2016;34:1651–1663